Giant fibroadenoma in postmenopausal female - Vandana Verma Ahluwalia; Prerna Singh Saharan; Ankita Chauhan (Wolters Kluwer Medknow Publications, 2018)
Giant fibroadenoma, with an overall incidence of <4%, is an uncommon variant of fibroadenoma. It is common in adolescent age group but sporadic in the elderly. The important differential is phyllodes tumor of the breast which also presents as rapidly enlarging mass. We herein report a case of a middle-aged woman with an unusually large fibroadenoma in the right breast and vascular calcification in the left breast.